2001
DOI: 10.1007/pl00011358
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Interleukin-1β Production and Gene Expression in Human Gingival Fibroblasts by Low-energy Laser Irradiation

Abstract: Human gingival fibroblast (hGF) cells reside in gingival tissues which are challenged frequently by oral bacteria. Lipopolysaccharide (LPS) from periodontal pathogens can penetrate gingival tissues and stimulate the production of interleukin-1beta (IL-1beta), which has been implicated in inflammation and bone resorption. The anti-inflammatory effects of low-energy laser irradiation have been reported, but the mechanisms of this biostimulatory effect have not been fully elucidated. Primary cultured hGF cells we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
48
0
5

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(56 citation statements)
references
References 24 publications
3
48
0
5
Order By: Relevance
“…These promote the expression of receptor activator of nuclear factor kappa-B ligand (RANKL) in synovial fibroblasts, the differentiation of osteoclasts and also induce MMP-3 production, all of which play parts in the destruction of the bone and joint [24][25][26][27] . In a previous in vitro study, the first author has demonstrated that Ga-Al-As diode laser irradiation (Panalas-1000: wavelength 830 nm, total energy density 7.9 J/ cm 2 ) significantly suppressed the production of PGE2, IL-1ß and PA in LPS stimulated human gingival fibroblast cell cultures [28][29][30] . Joint cartilage is composed of mainly type 2 collagen and chondroitin sulfate along with other extra-cellular matrix substances such as hyaluronic acid.…”
Section: Discussionmentioning
confidence: 99%
“…These promote the expression of receptor activator of nuclear factor kappa-B ligand (RANKL) in synovial fibroblasts, the differentiation of osteoclasts and also induce MMP-3 production, all of which play parts in the destruction of the bone and joint [24][25][26][27] . In a previous in vitro study, the first author has demonstrated that Ga-Al-As diode laser irradiation (Panalas-1000: wavelength 830 nm, total energy density 7.9 J/ cm 2 ) significantly suppressed the production of PGE2, IL-1ß and PA in LPS stimulated human gingival fibroblast cell cultures [28][29][30] . Joint cartilage is composed of mainly type 2 collagen and chondroitin sulfate along with other extra-cellular matrix substances such as hyaluronic acid.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature is reported that LLLT acts by reducing the inflammation process and accelerating wound healing in rats (29,54). Several authors showed that laser irradiation caused inhibition of PGE 2 through reduction of COX-2 mRNA levels (22,(55)(56)(57). In addition, low-level laser irradiation significantly inhibited the gene expression of IL-1β and IFN-γ (55,58).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, low-level laser irradiation significantly inhibited the gene expression of IL-1β and IFN-γ (55,58). IL-1β, PGE 2 , and IFN-γ are involved in different immune responses and in the acute phase of inflammatory processes (56,59). Also, IFN-γ is an important macrophage activator and plays an important role in the inflammatory process (59).…”
Section: Discussionmentioning
confidence: 99%
“…A 830-nm GaAlAs-laser irradiation inhibited prostaglandin E2 and IL-1b production and gene expression which might be of therapeutic benefit against the aggravation of gingivitis and periodontitis that accompanies bacterial infection [32,33]. Takema et al, 2000 described an 830-nm semiconductor laser-induced inhibition of the plasminogen activator (PA)-plasmin proteolytic system [34].…”
Section: Discussionmentioning
confidence: 99%